1993
DOI: 10.1084/jem.178.5.1617
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant soluble human Fc gamma RII: production, characterization, and inhibition of the Arthus reaction.

Abstract: SummaryA recombinant soluble form of human FcTRII (rsFcTRII) was genetically engineered by the insertion of a termination codon 5' of sequences encoding the transmembrane domain of a human FcTRII eDNA. Chinese hamster ovary cells were transfected with the modified cDNA and the secreted rsFcTRII purified from the tissue culture supernatant (to >95%, assessed by SDS-PAGE) using heat aggregated human immunoglobulin G (IgG) immunoaffinity chromatography. The IgG-purified rsFcTRII was relatively homogeneous (•31,00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 67 publications
2
41
2
Order By: Relevance
“…Our results suggest that CD32A-Ig is not able to compete with mouse Fc␥Rs for binding to IC either because the affinity of CD32A-Ig may be too low, or mouse Fc␥Rs and human CD32A may be binding to distinct regions of rabbit IgG. Thus our results, although supporting the observation reported by Ireino et al 52 that CD32A cannot practically block the IC-mediated inflammation, do, however, demonstrate the feasibility of using systemic administration of CD16A-Ig to block acute inflammation mediated by IC.…”
Section: Fc␥r Dimers Block Neutrophil Emigration 901contrasting
confidence: 56%
See 1 more Smart Citation
“…Our results suggest that CD32A-Ig is not able to compete with mouse Fc␥Rs for binding to IC either because the affinity of CD32A-Ig may be too low, or mouse Fc␥Rs and human CD32A may be binding to distinct regions of rabbit IgG. Thus our results, although supporting the observation reported by Ireino et al 52 that CD32A cannot practically block the IC-mediated inflammation, do, however, demonstrate the feasibility of using systemic administration of CD16A-Ig to block acute inflammation mediated by IC.…”
Section: Fc␥r Dimers Block Neutrophil Emigration 901contrasting
confidence: 56%
“…18,46,51 In contrast to our observations with recombinant soluble CD16A-Ig dimer presented here, an earlier study that used a recombinant soluble CD32A has concluded that parenterally administered soluble Fc␥Rs is not a practical approach to block IC-mediated inflammation. 52 Their conclusion was based on the observation that the systemically administered CD32A has a half-life of only 25 minutes and is unable to block Arthus reaction. This report also showed that soluble CD32A could block Arthus reaction only when administered locally along with the IC at a concentration of 5mg/mL.…”
Section: Fc␥r Dimers Block Neutrophil Emigration 901mentioning
confidence: 99%
“…However, more recent studies have suggested that IC-mediated inflammation in the RPA reaction is initiated via Fc␥ receptor-triggered pathways. For example, treatment of rats with recombinant soluble human Fc␥RII was shown to lead to a dose-dependent inhibition of the RPA response (5), and targeted deletion of the FcR ␥-chain resulted in markedly attenuated RPA reactions in mice (6,7). In addition, it was reported that in mice deficient in complement proteins C3, C4, or C5 the RPA reaction develops normally (8).…”
mentioning
confidence: 99%
“…Recent therapeutic approaches to the Arthus reaction focus on the use of recombinant soluble human complement receptor type I (Rossi et al, 1992) to control the activation of the complement cascade, the utilization of a recombinant soluble form of human Fc-yRII (Fc-yR, receptor for the Fc portion of IgG) genetically engineered to interfere with neutrophil activation via Fc-yRII, and the ensuing release of inflammatory mediators (Ierino et al, 1993); and the utilization of recombinant selectin chimeric molecules to block PMN recruitment (Mulligan et al, 1993). Another step for pharmacological modulation might be the antagonism of mediators released from PMN that could be particularly active either on their own or because of their central position Brfth Journal of Pharmacology (1995) 114.…”
Section: Introductionmentioning
confidence: 99%